Design And Development Of A Web-Based Event Organizer Management Application At CV. Cipta Abadi Organizer Using The Extreme Programming Method - Dwi Rama Rizki Santoso; Yudhi Raymond Ramadhan; Muhammad Rafi Muttaqin (International Journal of Health Engineering and Technology, 2026)
The increasing complexity of event organizer operations requires an integrated management application to improve administrative efficiency, coordination, and activity monitoring. This study aimed to design and develop a web-based Event Organizer Management application for CV. Cipta Abadi Organizer using the Extreme Programming (XP) method. This research employed a Research and Development approach with the Extreme Programming software development methodology. The population comprised all event management activities at CV. Cipta Abadi Organizer, while the sample focused on operational processes, including client management, vendor management, event scheduling, and event progress monitoring. Data were collected through observation and interviews, while data analysis was conducted by identifying user requirements, modeling the system using Unified Modeling Language (UML), implementing the application with Laravel and MySQL, and evaluating functionality through Test-Driven Development testing. The results indicate that the developed application successfully integrates client, vendor, event, rundown, and field log management, while all tested features function according to user requirements. It also improves data organization, operational coordination, and monitoring efficiency. In conclusion, the developed application is suitable for supporting integrated event organizer operational management and provides a practical digital solution for improving organizational performance.